The Influence of an Orthopedic, Manual Therapy Residency Program on Improved Knowledge, Psychomotor Skills, and Clinical Reasoning in Nairobi, Kenya - Cunningham, Shala; McFelea, Joni (Frontiers in Public Health, 2017)
Introduction: The purpose of this study was to describe the influence of a post-graduate orthopaedic manual therapy residency program in Kenya on the development of physical therapists (PT) knowledge and clinical reasoning related to the performance of a musculoskeletal examination and evaluation as compared to an experienced matched control group of PTs waiting to enter the program. Methods: A cross-sectional design was utilized in which 12 graduating residents and 10 PTs entering the residency program completed a live-patient practical examination to assess the knowledge, clinical reasoning, and psychomotor skills related to the examination and evaluation of musculoskeletal conditions. The assessment utilized was based on the tasks, procedures, and knowledge areas identified as important to advanced clinicians in the US as outlined by the Orthopaedic Description of Specialty Practice. Inclusion criteria included participation in or acceptance to the residency program, practice as a PT between 3 and 25 years, and 50% of workday being involved in direct patient care. Overall pass rates were analyzed using the Pearson chi-square and Fisher’s exact test to determine if the graduating residents achieved significantly higher scores than experienced matched controls consisting of PTs entering the residency program. Results: PTs completing a post-graduate orthopaedic manual therapy residency in Nairobi, Kenya achieved higher scores and passing rates compared to their colleagues that had not completed a residency program as determined by a live-patient practical examination. Graduating residents demonstrated statistically significant higher scores in the categories of examination, evaluation, and diagnosis. The average live-patient practical examination score for PTs without residency training was 38.2% and their pass rate was 0.0%. The average live-patient practical examination score for residency-trained PTs was 83.4% and their pass rate was 92.3%. These findings are statistically significant (p<0.001). Discussion: The study results suggest that the residency program had a positive influence on the residents’ ability to perform musculoskeletal examination and evaluation and to determine a treatment diagnosis. Future studies should be performed to determine if the improvements in assessment have a positive impact on clinical practice.